Accounting for visual field abnormalities when using eye-tracking to diagnose reading problems in neurological degeneration - Carla Daniela Guantay; Laura Mena-García; Miguel Angel Tola-Arribas; María José Garea García-Malvar; Marta Para-Prieto; María Gloria González-Fernández; Agustín Mayo-Iscar; José Carlos Pastor-Jimeno (Bern Open Publishing, 2024)
State-of-the-art eye trackers provide valuable information for diagnosing reading problems by measuring and interpreting people's gaze paths as they read through text. Abnormal conditions such as visual field defects, however, can seriously confound most of today's existing methods for interpreting reading gaze patterns. Our objective was to research how visual field defects impact reading gaze path patterns, so the effects of such neurological pathologies can be explicitly incorporated into more comprehensive reading diagnosis methodologies. A cross-sectional, non-randomized, pilot clinical study including 45 patients with various neurologic disorders and 30 normal controls was designed. Participants underwent ophthalmologic/neuropsychologic and eye-tracker examinations using two reading tests of words and numbers. The results showed that the use of the eye tracker showed that patients with brain damage and an altered visual field require more time to complete a reading-text test by fixating a greater number of times (p < 0.001); with longer fixations (p = 0.03); and a greater number of saccades in these patients (p = 0.04). Our study showed objective differences in eye movement characteristics in patients with neurological diseases and an altered visual field who complained of reading difficulties. These findings should be considered as a bias factor and deserve further investigation.